Turkey An Empirical Assessment of the Determinants of the Current Account Balance - Knight, David (World Bank E-Library Archive, 2019)
Turkey has moved rapidly from a current account that was relatively in balance up to the turn of the millennia, to sustaining relatively large current account deficits over the past 15 years. Using annual data from 1986 to 2017 and a jackknife model-averaging estimator, the paper estimates the relationship between the current account balance and a set of determinants that are broadly consistent with the cross-country literature. These determinants include private sector credit, public expenditure, real exchange rate changes, gross domestic product growth relative to the rest of the world, trade openness, international oil prices, foreign direct investment levels, past net foreign assets, inflation volatility, and global levels of uncertainty. The analysis then decomposes the predicted current account balance for five-year periods to illustrate the factors that have driven the current account over time. Over 2003-07, a large current account deficit became established in Turkey, driven by an expansion of credit to households and rapid gross domestic product growth, coupled with improved macroeconomic stability that supported higher spending and therefore imports. Since then, the negative effect of household credit has abated, but was replaced in 2008-17 by an expansion of credit to the corporate sector as a driver of the current account deficit. The current account balance in Turkey is also found to be less persistent than is typically found in the cross-country literature, implying that it adjusts more rapidly in response to shocks